Exploration of Segara Wukir Temple as a source of mathematics learning: An ethnomathematics study - Devina Anindya Kirana; Ririn Widiyasari (Universitas Hamzanwadi, 2025)
Mathematics and culture are two aspects that cannot be separated in daily life. Ethnomathematics is a bridge connecting the gap between culture and mathematics. The concept of ethnomathematics in this study aims to identify and describe the elements of ethnomathematics found in temple architecture, particularly those related to geometry and arithmetic sequences. The method in this study employs a qualitative research type with an ethnographic approach through an ethnomathematics design. The data sources used in this research were observations, documentation, and interviews. This research was conducted at Segara Wukir Temple, located in Ngobaran Beach, Kanigoro Village, Saptosari District, Gunungkidul Regency, in the Special Region of Yogyakarta, Indonesia. The results of the study reveal that Segara Wukir Temple is a cultural heritage site with high value; however, it has not been extensively researched as a source for learning mathematics. This research also contributes to the students' understanding of the application of mathematical concepts in the cultural heritage of temple architecture. In addition to enriching mathematical insights within a cultural context, this study can serve as a foundation for developing contextual, relevant, and engaging teaching materials for students.